Prognostic Value of Syndecan-1 in the Prediction of Sepsis-Related Complications and Mortality: A Meta-Analysis - Sun, Ting; Wang, Yuqiong; Wu, Xiaojing; Cai, Ying; Zhai, Tianshu; Zhan, Qingyuan (Frontiers in Public Health, 2022)
Aim: To assess the prognostic significance of syndecan-1 (SDC-1) in the prediction of complications and mortality risk in sepsis patients. Methods: We searched PubMed, EMBASE, Cochrane Library and Google Scholar databases. Meta-analysis was performed using the RevMan 5.4 software. Results: Eleven studies enrolling a total of 2318 patients were included. SDC-1 concentrations were significantly higher in the composite poor outcome group [standardized mean difference (SMD) 0.55; 95% CI 0.38- 0.72; p＜0.001], as well as in deceased patients (SMD 0.53; 95% CI 0.40-0.67; p＜0.001), patients with septic shock ( SMD 0.81; 95% CI 0.36-1.25; p＜0.001), and patients with acute kidney injury (SMD 0.48; 95% CI 0.33-0.62; p＜0.001). Conclusion: Baseline SDC-1 levels may be a useful predictor of complications and mortality.